Analisis Kepemimpinan Pendidikan Kompetensi Kepala Sekolah - Vika Widiana Lestari; Dhinda Anggita Prameswari; Maryani, Maryani; Rahmawati Rahmawati; Bahtiyar Heru Susanto (Journal Innovation In Education, 2024)
This research aims to find out the competence of school principals in educational leadership and examine the leadership competence of school principals who are effective in improving the quality of education. This research uses qualitative methods with data collection and analysis techniques by searching for literature through several books and scientific articles as well as other trusted sources. A leader is a figure who can be trusted and fosters a strong sense of loyalty towards his teammates. Leadership is one of several factors that determine an organization's ability to succeed. The principal is the person who leads the school. Effective leadership to organize, motivate, and influence leadership in organizations, which also summarizes performance and success. As an action, leadership functions to help achieve previously established work programs. Leaders encourage their subordinates to do things. According to Hersey and Blanchard, the four main dimensions of the principal's role are delegation, coaching, direction, and support. Becoming a school principal is not easy, because a school principal has various responsibilities and roles, one of which is being a strict school principal.